Anal canal duplication associated with presacral teratoma in a 5-year old girl - Jinyoung Park (Elsevier, 2017)
This report describes an extremely rare case of anal canal duplication associated with presacral teratoma in a 5-year-old girl who presented with perineal pain and constipation. Abdominopelvic computed tomography (CT) revealed a multiloculated heterogeneous mass measuring 5 cm in the presacral area. T2-weighted magnetic resonance imaging (MRI) showed a 4.5-cm sized multilocular cystic lesion with high signal intensity. The mass was surgically removed with coccyx. Histologically, the tumor showed components of bronchial and gastrointestinal mucosa, squamous epithelium, cartilage, fibrofatty tissue, and some exocrine glands. The histopathological diagnosis was mature teratoma. Eight months after surgery, the patient is doing well, with no recurrence of tumor.